PENTINGNYA MANAJEMEN KEUANGAN SEBAGAI UPAYA PENGEMBANGAN UMKM KERAJINAN TENUN TRADISIONAL DI DUSUN SADE LOMBOK TENGAH - Oktiani, Asri; Faezal, Faezal; Ramadhani, Ceila; Alfianti, Anggun Sukma; Maryanti, Sri (Devote: Jurnal Pengabdian Masyarakat Global, 2024)
MSMEs have an important role in improving the economy of a region, therefore MSMEs must know the application of financial management principles to develop their business. The problem that will be raised in this service activity is the important role of financial management in developing the traditional weaving craft business in Sade Hamlet. The output target of this community service activity is to change the mindset of weaving craft sellers who are donated by women that it is important to apply financial management to develop the business being carried out. The results of this activity are that the average business actor still does not keep financial records and also separates personal money from business capital and limited ability to count and is too lazy to record sales transactions so that the profits earned are not known with certainty.